TINJAUAN KRITIS TERHADAP PEMBOROSAN PANGAN: BESARAN, PENYEBAB, DAMPAK, DAN STRATEGI KEBIJAKAN (Forum Penelitian Agro Ekonomi, 2022)
Food loss and waste are the indicators of the 12 Sustainable Development Goals (SDGs) goals: ensure sustainable food consumption and production patterns. Indonesia is committed to achieving the targets set out in the SDGs, one of which is target 12.3: to reduce food loss and waste by half by 2030. Achieving this target is beneficial for attaining national food and nutrition security and environmental sustainability. This paper is a scientific review to analyse the magnitude, causes, impacts, and policy strategies for reducing food waste. The analysis results show that the percentage of food waste in the last two decades has tended to increase. The most significant proportion of food waste occurs at the household level. The leading cause is household food consumption patterns. It ranges from planning, purchasing, and processing up to consumption. Food waste has an impact not only on individuals but also on society in the form of economic, social and environmental losses. Therefore, efforts to reduce food waste should be comprehensive and sustainable, considering that changing people's food consumption behaviour takes a relatively long time. Another action is to change the mindset of each individual toward the value of food through formal education from an early age and non-formal socialisation by utilising various communication media.